ASM655: Management of information security / Faculty of Business Management - UiTM, Faculty of Business Management (2018)
The course focuses on the managerial aspects of information security, such as access control models, information security governance, and information security program assessment and metrics. Coverage on the foundational and technical components of information security is included to reinforce key concepts. This course offers a unique overview of information security from a management perspective while maintaining a finger on the pulse of industry changes and academic relevance. This course also reviews some of the recent issues in information security and how to secure information in modern organizations.